Estrutura e função da proteína YacG de Klebsiella pneumoniae e seus derivados peptídicos - Garcia, Anderson [UNESP] (2015)
YacG belongs to zinc-finger's protein family discovered in E. coli. Its biological function is connected to the catalytic inhibition of DNA gyrase and stress metabolism in prokaryotes. This protein inhibits DNA gyrase (gyrase) through a bipartite mechanism where the zinc-finger domain prevents the DNA ligation to the B subunit (GyrB) and the C-terminal bindings to the A subunit (GyrA). Although it is classified as a gyrase inhibitor neither the inhibition activity of YacG from E. coli and other microorganisms against other DNA topoisomerases nor the biological activity of fragments in cellular assays has been evaluated until present. In this study, YacG from Klebsiella pneumoniae was obtained by heterologous expression and derivative peptides from this protein were synthesized by the solid-phase method. The synthetic peptides were designed to keep the native region of zinc-finger (YacGAG1), to substitute cysteines to serines (YacGAG4), to alanine (YacGAG5), to histidine (YacGAG6 and YacGAG8) and also having only the C-terminal region (YacGAG7). The inhibition assays of gyrase by the peptides and the native protein revealed that YacG, YacGAG4, YacGAG4 e YacGAG7 inhibited this enzyme and the human topoisomerase IIα (htopoIIα). However, the same was not observed for the native fragment YacGAG1, which inhibited only the htopoIIα. The results are in agreement with literature showing that solely the C-terminal region is able to inhibit the gyrase. The assays of fluorescence anisotropy indicated that these synthetic peptides interact with GyrA. Besides inhibiting the gyrase and the htopoIIα, these peptides also revealed bacteriostatic activity against gram-negative and gram-positive bacteria. A computational study by applying a molecular dynamics protocol highlighted the importance of residues I47, R46 and W40 from YacG in the process of molecular recognition and interaction with GyrB. The results...